Multilingual education and sustainable diversity work : from periphery to center - Skutnabb-Kangas, Tove; Heugh, Kathleen (Routledge, 2012)
"Drawing on the most powerful and compelling research data to date and connecting this research to linguistic human rights, this book explores the conditions and practices of robust bilingual and multilingual educational innovations in both system-wide and minority-settings and what it is that makes these viable. It demonstrates how, in poor countries where educational practices are inclusive of linguistic diversity and responsive to local conditions and community participation, implementation of bilingual education even within limited budgetary investment can be successful"--